PARTICIPATION AND POWER DISTRIBUTION IN MUSRENBANGDES: ANALYSIS OF VILLAGE GOVERNANCE - Diah Ayu Pratiwi; Virda Sofwatun Nida; Dimas Saputra; TB. Muhammad Raffi Adzikra (Jurnal EL-RIYASAH, 2026)
Community participation is a fundamental principle of village governance and decentralized development planning in Indonesia. Through the Village Development Planning Meeting (Musrenbangdes), citizens are expected to contribute to determining development priorities and influencing village policy decisions. However, the existence of participatory forums does not necessarily ensure an equitable distribution of authority between citizens and village governments. This study analyzes the quality of community participation in Musrenbangdes by examining actor involvement, deliberative processes, and the distribution of decision-making power. This research employed a qualitative case study approach in Pancaregang Village. Data were collected through in-depth interviews, observation, and document analysis and analyzed using the interactive model of Miles, Huberman, and Saldaña, supported by NVivo 12 Plus. Arnstein’s Ladder of Participation was used as the analytical framework. The findings reveal that community participation remains limited and uneven. Although citizens are formally involved through deliberative forums and proposal submission, agenda-setting, proposal evaluation, and priority determination continue to be dominated by village authorities. As a result, participation functions primarily as a consultative mechanism rather than a collaborative decision-making process. This study concludes that participation in Pancaregang Musrenbangdes is situated at the Consultation level of Arnstein’s Ladder of Participation. The findings highlight a consultation–partnership gap in village governance, where decentralization expands opportunities for participation without substantially redistributing decision-making power